Direct recording of action potentials of cardiomyocytes through solution processed planar electrolyte-gated field-effect transistors - Kyndiah, Adrica; Dipalo, Michele; Molazemhosseini, Alireza; Viola, Fabrizio Antonio; Modena, Francesco; Iachetta, Giuseppina; Zorn, Nicolas; Berger, Felix J.; Zaumseil, Jana; Caironi, Mario; De Angelis, Francesco (Sensors and actuators. B, Chemical, 2023)
To achieve intracellular recording of action potentials by using simple devices that can be easily fabricated and processed is crucial in cardiology and neuroscience. Present tools and technology include invasive patch clamp technique, 3D nanostructures often combined with electro/opto poration methods and nanodevices such as nanowire field-effect transistors. However, these approaches mostly require complex manufacturing processes or are invasive. In this work, we report the spontaneous intracellular-like recording of cardiac cells using a cost-effective, planar Electrolyte-Gated Field-Effect Transistor (EGFET) based on solution-processed polymer-wrapped monochiral semiconducting single-walled carbon nanotubes (SWCNTs). By simply turning on the transistor, spontaneous recordings of intracellular-like action potentials of human induced pluripotent stem cells derived cardiomyocytes are enabled. In addition, we demonstrate that the same planar EGFET can also be employed as a platform for electroporation with significant device performance and cell viability. The simplicity of the device combined with the high signal to noise ratio opens up new opportunities for low-cost, reliable, and flexible biosensors and arrays for high quality parallel recording of cellular action potentials.
Gesehen am 08.11.2023